Band Pull-Apart Exercise: Effects of Movement Direction and Hand Position on Shoulder Muscle Activity - Takumi Fukunaga; Connor Fedge; Timothy Tyler; Michael Mullaney; Brandon Schmitt; Karl Orishimo; Malachy McHugh; Stephen Nicholas (International Journal of Sports Physical Therapy)
# Background/Purpose